One‐Step Synthesis of NiFe Layered Double Hydroxide Nanosheet Array/N‐Doped Graphite Foam Electrodes for Oxygen Evolution Reactions. Issue 7 (24th July 2019) - Li, Rui; Xu, Jingsong; Pan, Qifa; Ba, Jingwen; Tang, Tao; Luo, Wenhua
Abstract: Developing cost‐effective and highly efficient oxygen evolution reaction (OER) electrocatalysts is vital for the production of clean hydrogen by electrocatalytic water splitting. Here, three dimensional nickel‐iron layered double hydroxide (NiFe LDH) nanosheet arrays are in‐situ fabricated on self‐supporting nitrogen doped graphited foam (NGF) via a one‐step hydrothermal process under an optimized amount of urea. The as prepared NiFe LDH/NGF electrode exhibits a remarkable activity toward OER with a low onset overpotential of 233 mV and a Tafel slope of 59.4 mV dec −1 as well as a long‐term durability. Such good performance is attributed to the synergy among the doping effect, the binder‐free characteristic, and the architecture of the nanosheet array. Abstract : One‐step, high stability : Growth of NiFe layered double hydroxide (NiFe LDH) nanosheet arrays and preparation of N‐doped graphite foam (NGF) are concurrently obtained via a one‐step hydrothermal method. The as‐obtained electrode exhibits a low onset overpotential of 233 mV with a long‐term stability toward oxygen evolution reaction.